Uji Kemiripan Kalimat Judul Tugas Akhir dengan Metode Cosine Similarity dan Pembobotan TF-IDF - Indra Mawanta; T S Gunawan; Wanayumini Wanayumini (STMIK Budi Darma, 2021)
Deli Husada Health Institute is a health campus that has been established for 34 years, currently it has 30000 students, each student at the final level will submit a final project of study program every year, each student before doing his final project report must provide the title of an assignment report. Finally, to the study program, to reduce the level of similarity in the title of the student's final report, the study program usually conducts a manual check, the result that appears is that it is not effective in determining the title of the final project for students, so that it creates quite a lot of similarities between students. So that many final project reports look the same. With the above conditions, the Sentence Similarity Test of the Final Project Title was carried out with the Cosine Similarity Method and TF-IDF Weighting at the Deli Husada Delitua Health Institute Campus. At the end of the test results on the training data against the training data, the results obtained were 43% of the titles in Submitted is not eligible to be submitted again and 53% is eligible to be submitted as the title of the final project because it has high similarities to the title of the final project report. And get the average time 0.12117 in minutes